Effects of Neuromuscular Control Training and Proprioceptive Exercise on Pain, Pelvic Stability, and Functional Outcomes in Patients with Sacroiliac Joint Dysfunction (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Objective: Evaluate the efficacy of neuromuscular control training combined with proprioceptive exercises on pain reduction, pelvic stability, and functional outcomes in patients with sacroiliac joint (SIJ) dysfunction compared to standard care.Methods: A prospective, randomized controlled trial with 124 participants (intervention n=62, control n=62) conducted over 12 weeks at three academic medical centers. Intervention group received 2-3 supervised sessions per week of structured neuromuscular training targeting core stabilizers and proprioceptive exercises. Control group received standard care consisting of patient education and general exercise. Primary outcomes assessed at baseline, weeks 4, 8, 12, and 24: Visual Analog Scale (VAS) pain (0-10), Posterior Superior Iliac Spine Distance Ratio (PSIS-DR) for pelvic stability assessment, and Lower Extremity Functional Scale (LEFS, 0-80 points). Secondary outcomes included Oswestry Disability Index (ODI), Short Form-36 (SF-36) quality of life measures, proprioceptive function, and core muscular strength.Results: Intention-to-treat analysis of 121 participants (97.6% retention). Intervention group demonstrated statistically significant and clinically meaningful improvements across all primary outcomes. VAS pain reduction: 5.2±1.8 points (77% improvement) in intervention versus 1.3±1.5 points (19% improvement) in controls (p<0.001, 95% CI: 3.1-4.9). Pelvic stability improvement: 3.4±1.1 mm (41.5% reduction in asymmetry) in intervention versus 0.6±0.8 mm (7.1% reduction) in controls (p<0.001, 95% CI: 2.4-4.4). LEFS functional improvement: 28.5±6.7 points (88% recovery) in intervention versus 7.2±5.3 points (23% recovery) in controls (p<0.001, 95% CI: 18.3-23.8). Large effect sizes (Cohen's d) demonstrated for all primary outcomes (d=1.8-2.6). Benefits sustained at 6-month follow-up with minimal regression. 68% of intervention participants achieved clinically normal pelvic alignment versus 11% in controls (p<0.001). Session adherence: 95.2% (34.2±2.1 of 36 prescribed sessions). Home exercise compliance: 78.4%. Adverse events: no serious adverse events; mild self-limiting muscle soreness in 30% of intervention participants during week 1-2.Conclusion: Structured neuromuscular control training combined with systematic proprioceptive exercise is highly effective for managing sacroiliac joint dysfunction, providing substantial and durable improvements in pain, pelvic stability, and functional capacity. This conservative intervention demonstrated superior efficacy compared to standard care with excellent safety profile and high patient adherence. Evidence supports position as first-line management for SIJ dysfunction.